Use of complementary therapies for side effect management in breast cancer: evidence and rationale. (August 2016) - Roe, Kelly; Visovatti, Moira Kirvan; Brooks, Trevor; Baydoun, Mohamad; Clark, Patricia; Barton, Debra L
Women diagnosed with breast cancer can experience chronic side effects after curative treatment concludes, negatively impacting survivorship. The most prevalent side effects addressed in the medical and nursing literature include symptoms such as hot flashes, fatigue, myalgias/arthralgias and cognitive impairment. Complementary therapies, particularly natural products including herbs, dietary supplements, vitamins, minerals, and probiotics, and mind–body techniques that include such modalities as yoga, meditation, massage, acupuncture, relaxation, tai chi and hypnosis show promise for treatment of some of these symptoms associated with cancer care. However, the research in this area is nascent and much more work is needed to understand symptom physiology and mechanisms of action of complementary therapies. The purpose of this paper was to summarize key evidence from Phase II and III randomized clinical trials in order to provide guidance to distinguish promising versus nonpromising interventions for symptom management.